Nitrate-Functionalized poly(ε-Caprolactone) Small-Diameter Vascular Grafts Enhance Vascular Regeneration via Sustained Release of Nitric Oxide - Yang, Sen; Zheng, Xueni; Qian, Meng; Wang, He; Wang, Fei; Wei, Yongzhen; Midgley, Adam C.; He, Ju; Tian, Hongyan; Zhao, Qiang (Frontiers in Bioengineering and Biotechnology, 2021)
Artificial small-diameter vascular grafts (SDVG) fabricated from synthetic biodegradable polymers, such as poly(ε-caprolactone) (PCL), exhibit beneficial mechanical properties but are often faced with issues impacting their long-term graft success.. Nitric oxide (NO) is an important physiological gasotransmitter with multiple roles in orchestrating vascular tissue function and regeneration. We fabricated a functional vascular graft by electrospinning of nitrate-functionalized poly(ε-caprolactone) that could release NO in a sustained manner via stepwise biotransformation in vivo. Nitrate-functionalized SDVG (PCL/NO) maintained patency following abdominal arterial replacement in rats. PCL/NO promoted cell infiltration at 3-months post-transplantation. In contrast, unmodified PCL SDVG showed slow cell in-growth and increased incidence of neointima formation. PCL/NO demonstrated improved endothelial cell (EC) alignment and luminal coverage, and more defined vascular smooth muscle cell (VSMC) layer, compared to unmodified PCL SDVG. In addition, release of NO stimulated Sca-1+ vascular progenitor cells (VPCs) to differentiate and contribute to rapid luminal endothelialization. Furthermore, PCL/NO inhibited the differentiation of VPCs into osteopontin-positive cells, thereby preventing vascular calcification. Overall, PCL/NO demonstrated enhanced cell ingrowth, EC monolayer formation and VSMC layer regeneration; whilst inhibiting calcified plaque formation. Our results suggested that PCL/NO could serve as promising candidates for improved and long-term success of SDVG implants.